2002
DOI: 10.1086/344463
|View full text |Cite
|
Sign up to set email alerts
|

CorynebacteriumSpecies Isolated from Patients with Mastitis

Abstract: Corynebacteria were isolated from breast tissue, pus, or deep wound swabs of 24 women; the most common species isolated was the newly described Corynebacterium kroppenstedtii, followed by Corynebacterium amycolatum and Corynebacterium tuberculostearicum. Gram-positive bacilli were seen in samples sent for culture or in histological specimens for 12 women, and 9 of the 12 women from whom adequate histological specimens were obtained had conditions that met the criteria for granulomatous lobular mastitis, a chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(186 citation statements)
references
References 11 publications
5
169
1
6
Order By: Relevance
“…In literature, breast tissue infections due to C. kroppenstedtii has been reported more frequently in comparison to C. amycolatum. [2,8] This may be because of the lipophilic nature of C. kroppenstedtii.C. accolens which is also lipophilic has also been reported from case of breast abscess associated with granulomatous mastitis.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature, breast tissue infections due to C. kroppenstedtii has been reported more frequently in comparison to C. amycolatum. [2,8] This may be because of the lipophilic nature of C. kroppenstedtii.C. accolens which is also lipophilic has also been reported from case of breast abscess associated with granulomatous mastitis.…”
Section: Case Reportmentioning
confidence: 99%
“…accolens which is also lipophilic has also been reported from case of breast abscess associated with granulomatous mastitis. [2,9] It has been stated that the significance of Corynebacteria can be determined by the presence of Gram positive bacilli along with PMNs in the clinical sample. [10] The occurrence of Gram positive bacilli along with many PMNs and pure growth of Corynebacterium amycolatumin our case strongly signifies this organism to be the only causative pathogen for the infection.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Коринебактерии могут образовывать грануломатозные структуры глубоко в ткани молочной железы. Ранее их необоснованно исключа-ли из списка возбудителей мастита [18,19].…”
Section: рисунок 2 схематическое представление этиопатогенеза острогunclassified
“…Taylor et al isolated Corynebacteria from breast tissue in 62 patients, who were diagnosed with GLM histologically, and 54.8% patients were bacteriapositive. Paviour et al 7 carrieded on a research of 24 patients, and observed Corynebacteria in 12 cases by hostopathological evaluation and diagnosed 9 cases with idiopathic granulomatous mastitis (IGM). Corynebacterium kroppenstedtii was the most frequently detected species in the studies mentioned above.…”
Section: Microbiology Agentsmentioning
confidence: 99%